Combined Numerical and Experimental Investigation of the Cavitation and Erosion of Submerged Self-resonating Waterjet. (August 2019) - Cui, Lihua; Ma, Fei; Cai, Tengfei; Pan, Yan; Liu, Boshen; Qiu, Linbin
Abstract: In ocean exploitation of deep-sea mineral, cavitation always occurs. In this paper, a model based on the Rayleigh-Plesset equation for researching the cavitation of the self-resonating waterjet was build up. A three-dimensional Computational Fluid Dynamic (CFD) analysis method to demonstrate the possibly of using the pressure distribution phenomenon prediction the evolution of cavitation bubbles. Frequency bands of numerical simulations were in good agreement with experimental data. Based on this, we obtain the shedding frequency of the bubbles, researched the erosions effect. The results validate the proposed scheme, which could be used to adjust the erosions domains.